La atención en la lecto-escritura de los niños/as del segundo año de educación básica de la unidad educativa municipal Heroes del Cenepa de la ciudad de Loja durante el periodo marzo 2013 a marzo del 2014 - Chacha Carrión, Victoria Mireya (2014)
THE ATTENTION ON LITERACY WITH CHILDREN OF SECOND YEAR OF BASIC EDUCATION AT UNIDAD EDUCATIVA MUNICIPAL HEROES DEL CENEPA OF Loja CITY DURING MARCH 2013 TO MARCH 2014. Reason why the researcher pursued as general objective :to learn how attention influences on literacy with children of second year of Basic Education at UNIDAD EDUCATIVA MUNICIPAL HEROES DEL CENEPA OF Loja city. The theoretical framework on which the research process was based were concepts of care and literacy, forms of care, stages of literacy and the relationship between attention and literacy. This research followed a logical and systematic process. The population was of 307 students and 15 teachers from which a sample of 40 children of second year of basic education was taken, and five teachers. To collect the reliable information, a survey for teachers, a reading test and Writing ( Ricardo Olea ) and faces test for children was used. At the end of the research work, it is concluded that :the children of second year of basic education , present a divided form of attention. The following recommendation was proposed for teachers :to pay attention to the various forms that children present in order to solve them, the strategies and learning techniques for a good school performance